Wear Analysis and Corrective Maintenance Worm Screw Press at PT. XYZ - Ihsan Hamdy, Muhammad; Taslim, Rika; Andhen Sury, Nyvia (Universitas Negeri Padang, 2024)
PT. XYZ is one of the palm oil processing companies located in the Riau area. The purpose of this study was to determine the right type of machine maintenance, especially for the worm screw press, because this part often experiences wear and tear which affects the results of pressing palm oil into oil. Wear and tear can partially reduce the surface of the machine and affect the performance of each machine. The service life of the worm screw press provided by the manufacturer is 1000 hours. However, usage at the Sebanga Multi Sawit factory reaches 1300-1500 hours. This proves that there is a need for further studies on good maintenance methods on screw press machines. The calculation of the wear rate and the depth of wear is used to determine the amount of wear that occurs. Solutions that can be done are welding, pack carburizing, and flame hardening on the worm screw press.